Fifty years on maritime transportation - Marielle Christiansen; Kjetil Fagerholt; David Pisinger (EURO Journal on Transportation and Logistics)
This paper gives a detailed overview of the last 50 years of research in maritime transportation, with special focus on operations research techniques applied to the seaside operations. We describe the evolution in industrial, tramp and liner shipping, identify the driving trends, and discuss future challenges.